Experiential Marketing to Improve Interest In Buying MSME Products of Powder Coffee Tugu Sari Pupuan Bali - Juniasih, Ida Ayu Komang; Nona, Reyna Virginia; Suastama, Ida Bagus Radendra; Setiyarti, Tettie; Wijayanthi, Ida Ayu Trisna (Jurnal Manajemen (Edisi Elektronik), 2023)
This study aims to identify important indicators in experiential marketing to increase interest in buying MSME products with Tugu Sari Pupuan stamped coffee powder, Bali. This study uses a quantitative method research design to test models and instruments that have been developed by previous researchers through inferential statistics, namely by using Structural Equation Modeling, with the Partial Least Square (PLS) approach. The population in this study were coffee connoisseurs with 90 respondents. The independent variables used in this study were sense experience, feel experience, think experience, act experience, and relate experience. The results showed that, to increase interest in buying MSME products, Tugu Sari coffee was strongly influenced by act experience (0.724) with the highest indicators being economical packaged products (0.945), unique products (0.937), and products with character (0.921). The findings in this study are useful for increasing people’s buying interest in coffee MSME products. The most important indicators for increasing interest in buying MSME products are variables that come from relate experience, namely consumers recommending them to others